A Puzzle for Philosophers - Lo Guercio, Nicolás Francisco (2013)
In the paper I tackle a puzzle by Goldberg (2009) that challenges all of us as philosophers. There are three plausible thesis, separately defensible, that together seem to lead to a contradiction: 1) Reliability is a necessary condition for epistemic justification. 2) On contested matters in philosophy, philosophers are not reliable. 3) At least some philosophical theses regarding contested matters in philosophy are epistemically justified. In this paper I will assess the status of the puzzle and attempt to solve it. In the first section, I'll present the puzzle with a little more detail. Secondly, I'll provide some general arguments to show that the alleged puzzle is not a legitimate one. Finally, in section 3, I will argue that even assuming that the puzzle can be coherently formulated, Goldberg's arguments in favor of premise (2) are either unsound or too limited in their scope in order to represent a significant or interesting problem for philosophers.